Front Cover: Bone tissue engineering for treating osteonecrosis of the femoral head (EXP2 2/2023). Issue 2 (20th April 2023) - Bian, Yixin; Hu, Tingting; Lv, Zehui; Xu, Yiming; Wang, Yingjie; Wang, Han; Zhu, Wei; Feng, Bin; Liang, Ruizheng; Tan, Chaoliang; Weng, Xisheng
Abstract : Osteonecrosis of the femoral head (ONFH) is a progressive and devastating disease with an unclear etiology. During the last decades, great progress has been made in ingenious bone tissue engineering for ONFH treatment. In this contribution, we present a comprehensive Review to summarize the state‐of‐the‐art progress made in bone tissue engineering for treating ONFH.